Digital Literacy and Teaching Experience as Predictors of Pedagogical Competence in the Digital Era - Theresia Anggraini; Masduki Ahmad; Ivan Hanafi (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This study investigates the influence of digital literacy and teaching experience on teachers' pedagogical competencies and essential skills, which are crucial for ensuring effective and high-quality learning processes. In the digital era, digital literacy empowers teachers to integrate technology into teaching, while teaching experience shapes their ability to manage classrooms and deliver effective instruction. Despite the increasing importance of these factors, there still needs to be a gap in understanding how they interact to enhance pedagogical competence. Data was gathered by administering questionnaires to 136 private senior high school teachers in the Cengkareng sub-district, who were chosen proportionately at random using a quantitative technique and multiple linear regression analysis. The findings indicate that digital literacy and teaching experience significantly influence teachers' pedagogical competence. These results underscore the importance of promoting digital literacy and fostering teaching experience as strategic measures to improve pedagogical competence. The study suggests that targeted professional development initiatives should enhance these factors to improve teaching effectiveness and ultimately elevate school learning outcomes.